Managing the entrepreneurial university : legal issues and commercial realities - Toma, J. Douglas (New York : Routledge, 2011)
The objective of this volume is to gather theoretical and empirical research on universities and their entrepreneurial ecosystems in order to better grasp the connections between universities and their surrounding environments to promote a sustainable performance. The book seeks to provide a better understanding of universities and their entrepreneurial characteristics and the ways in which they participate in an ecosystem that is important for business and industry transformation as well as how they function within the university/industry/government/third sector relationship nexus. The book will invite contributions that enable the systematisation of the existing literature while simultaneously building theory, empirically testing existing theories and contributing towards a future research agenda. Analysis of the various spatial helices (i.e., triple, quadruple and quintuple) will also provide a unique element for the advancement of both theory and practice in this field of study.
Includes bibliographical references and index.
Keywords: Education, Higher -- Law and legislation -- United States; Universities and colleges -- Law and legislation -- United States